The Implementation of Authentic Assessment in Vocational High School 1 Kuala Cenaku - Ekawati, Dian (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Teaching and learning are not complete without assessment which is needed to measure the students capability and achievement in language learning. Assessment is an essential activity and as an integral part of teaching learning process and it is used to see whether the teaching and learning process can run as expected and reach the desired objectives. One particular form to assess the students reading comprehension is by using authentic assessment. Authentic assessment requires demands on teachers professional skills since it calls for independent judgment and interpretation of student performance. It takes times and careful planning to be used effectively However, most teachers do not feel adequately prepared and mastered in assessing their students by using an authentic assessment. The problems appear while the teachers start to apply it. The main contribution of this study is to determine the problems of two English teachers in implementing and applying an authentic assessment on reading comprehension. Using descriptive qualitative method and semi-structured interview administered to two English teachers, the researcher observes directly to confirm the data obtained from English teachers who use authentic assessment in their reading comprehension class and this study highlights some findings those are the teachers problems in implementing an authentic assessment. Based on the observation and interview the researcher finds several difficulties that faced by the teacher in preparing, applying and implementing the authentic assessment on students reading comprehension.